The relative age effect and physical fitness characteristics in German male tennis players - Ulbricht, A.; Fernandez-Fernandez, J.; Mendez-Villanueva, A.; Ferrauti, A. (Journal of Sports Science & Medicine, 2015)
The aims of the study were to test: 1) whether the relative age effect (RAE) was prevalent in young (U12-U18) German male tennis players; 2) the potential influence of age and/or skill level on RAE and 3) whether maturity, anthropometric and fitness measures vary according to birth date distribution in elite youth tennis players. For the present study the following male populations were analysed: Overall German population (n = 3.216.811), all players affiliated to the German Tennis Federation (DTB) (n = 120.851), players with DTB official ranking (n = 7165), regional (n = 381) and national (n = 57) squads (11-17 years old), as well as the top 50 German senior players were analyzed. RAEs were more prevalent at higher competitive levels with more players born in the first quarter of the year compared with the reference population for ranked (29.6%), regional (38.1%) and national (42.1%) players. No systematic differences were found in any of the maturity, anthropometric and fitness characteristics of the regional squad players born across different quarters. RAEs are present in the DTB competitive system and it was more pronounced at higher competitive levels. Compared with early born, late born players who were selected into elite squads did not differ in maturation, anthropometric and fitness characteristics.